2021
DOI: 10.1007/s10668-020-01109-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and economic sustainability in public contexts: the impact of hand-drying options on waste management, carbon emissions and operating costs

Abstract: Due to the high density of users hosted everyday, public buildings are important producers of waste and emissions of greenhouse gases (GHGs). Public restrooms play an underrated role in waste generation and GHG emissions, especially if paper towels are used as the hand-drying method. The choice of the hand-drying method (i.e., paper towels vs. electrical hand dryers) also affects the economic balance of a public institution, involving costs for the purchase of hand-drying materials/apparatuses, energy and wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…We conducted two earlier studies with the ABHR procedures and found similar results among nurse students [ 12 , 13 ]. It has been demonstrated in a study that up to 86% of test subjects in a real world setting use only small doses of alcohol disinfectant, if not instructed otherwise, as low as approximately 0.75 mL [ 22 ]. In the present study, 46% (12 out of 26 participants) in group B used at least two doses (3 mL) from the dispenser, as recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted two earlier studies with the ABHR procedures and found similar results among nurse students [ 12 , 13 ]. It has been demonstrated in a study that up to 86% of test subjects in a real world setting use only small doses of alcohol disinfectant, if not instructed otherwise, as low as approximately 0.75 mL [ 22 ]. In the present study, 46% (12 out of 26 participants) in group B used at least two doses (3 mL) from the dispenser, as recommended by the manufacturer.…”
Section: Discussionmentioning
confidence: 99%
“…In the environmental cluster, studies have highlighted the need to reduce carbon emissions (Coller et al, 2021;Khurshid et al, 2022), use renewable energy to improve energy efficiency (Irfan et al, 2021;Xu et al, 2021), biodiversity (Teraa & Bencherif, 2022), and the importance of preserving the environment for poor communities (Forkuor & Korah, 2023;Ho et al, 2022).…”
Section: The Most Frequent Research Topicsmentioning
confidence: 99%
“…The criticalities of the local waste management consist in the destination of residual MSW, especially in Trentino, the southern province. This area is characterised by high selective collection rates, partly favoured by the tariff in force, which penalise the production of residual MSW and bad selective collection behaviours by the users [27][28][29]. Most of the flow of the residual waste produced here has been historically sent to MSW landfills, which are now reaching saturation.…”
Section: Case Studiesmentioning
confidence: 99%